A prospective study of arthroscopic evaluation of patients with chronic shoulder pain - Bhor, Pramod; Kale, Sachin Y.; Singh, Shikhar D.; Dhar, Sanjay B.; Garg, Abhinav; Bukalsaria, Divyesh (International Journal of Research in Orthopaedics, 2017)
Background: Shoulder pain is a common musculoskeletal complaint that may be due either to intrinsic disorders of the shoulder or referred pain. In this study, we aimed to find out the sensitivity and specificity of the clinical and radiological methods in diagnosing the chronic shoulder problems and to compare clinical and radiological diagnosis with arthroscopic diagnosis. Methods: After obtaining approval of the institutional ethics committee, we enrolled patients who presented with chronic shoulder pain in the outpatient clinic of Department of Orthopedics, DY Patil Medical College and Hospital, Navi Mumbai from August 2003 till August 2005. We obtained historical data of each patient in detail and made clinical, radiological and arthroscopic diagnosis. The findings from each diagnostic modality were compared and analysed. Results: During the study period, 34 patients were enrolled in the study. Injury was traumatic in 32% of the patients and 50% of all patients were heavy workers by occupation. Half of all the patients had pain in shoulder for more than 6 months. Clinical diagnosis of biceps tendinitis was made in 44% of patients, but radiological and arthroscopic diagnosis of biceps tendinitis was made in 18% and 12% respectively. Impingement was diagnosed in 29% patients clinically, in 15% patients radiologically and in 21% patients arthroscopically. Rotator cuff injury was diagnosed in 26% patients clinically, in 41% patients radiologically and in 67% patients arthroscopically. Conclusions: Findings from this single centre study suggest that arthroscopy can diagnose and treat conditions causing chronic shoulder pain, which is cost effective as well.